Sex Differences in Dendritic Spine Formation in the Hippocampus and Animal Behaviors in a Mouse Model of Hyperthyroidism - Niiyama, Tetsushi; Kuroiwa, Mahomi; Yoshioka, Yusaku; Kitahara, Yosuke; Shuto, Takahide; Kakuma, Tatsuyuki; Ohta, Keisuke; Nakamura, Kei-ichiro; Nishi, Akinori; Noda, Mami (Frontiers in Cellular Neuroscience, 2020)
Thyroid hormones are critical for the regulation of development and differentiation of neurons and glial cells in the central nervous system (CNS). We have previously reported the sex-dependent changes of glial morphology in the brain under the state of hyperthyroidism. Here, we examined sex-dependent changes in spine structure of granule neurons in the dentate gyrus of hippocampus in male and female mice with hyperthyroidism. Using FIB/SEM (focused ion beam/scanning electron microscopy), three-dimensional reconstructed structures of dendritic spines in dentate granule cells were analyzed. Dendritic spine density in granule cells increased significantly in both male and female mice with hyperthyroidism. The decrease in spine volume was observed only in female mice. These findings suggest that hyperthyroidism induces the formation of spines with normal size in male mice but the formation of spines with small size in female mice. To evaluate an outcome of neuronal and previously observed glial changes, behavioral tests were performed. Male mice with hyperthyroidism showed increased locomotor activity in the open field test, while female mice showed elevated immobility time in the tail suspension test, reflecting depression-like behavior. Although direct link between changes in spine and behavioral modifications requires further analysis, our results may help to understand gender-dependent neurological and psychological symptoms observed in patients with hyperthyroidism.